COMPETITIVE ADSORPTION OF FURFURAL AND PHENOLIC COMPOUNDS ONTO ACTIVATED CARBON IN FIXED BED COLUMN (Journal of Engineering, 2006)
For a multicomponent competitive adsorption of furfural and phenolic compounds, a mathematical model was built to describe the mass transfer kinetics in a fixed bed column with activated carbon. The effects of competitive adsorption equilibrium constant, axial dispersion, external mass transfer and intraparticle diffusion resistance on the breakthrough curve were studied for weakly adsorbed compound (furfural) and strongly compounds (parachlorophenol and phenol). Experiments were carried out to remove the furfural and phenolic compound from aqueous solution. The equilibrium data and intraparticle diffusion coefficients obtained from separate experiments in a batch absorber, by fitting the experimental data with theoretical model. The results show that the mathematical model includes external mass transfer and pore diffusion using nonlinear isotherms, provides a good description of the adsorption process for furfural and phenolic compounds in fixed bed adsorber.